THE DOCTRINE OF KARMA IN BUDDHISM AND SIKHISM: A COMPARATIVE STUDY - Sivasai, Chintala Venkata (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Karma is an action, work, or deed. The principle states that an individual's actions and intent affect their future. Many religions and cultures believe that doing good deeds leads to positive Karma and happiness. In contrast, evil deeds cause suffering and bad Karma. Originally from ancient India, Karma is believed in Buddhism, Hinduism, Sikhism, and Jainism.word kamma in Pali has multiple meanings. The phrase "action or deed" is meant literally. "Good and bad volition" is the commonly understood interpretation (Kusala Akusala Cetana). The law of moral causation, also known as "action (Kamma) and reaction (Vipaka) in the ethical realm," is based on kamma. Most deliberate acts are referred to as kammas. The Buddha and Arahants are the exceptions; they have destroyed all of their passions and so do not accumulate new Kamma. However, the Buddha was the one who developed and provided a thorough explanation of the Kamma and Rebirth doctrine found in the old Buddhist writings. Sikhism believes in lifelong good and bad karma. Karma decides where atma goes in the next life. According to Sikh belief, positive actions result in good karma, while negative actions result in bad karma. Guru Nanak accepted both the transmigration of souls theory and the doctrine of karma. Sagun Bhakti Sect was represented by Ramanand. The body is the field of karma and in this age; whatever shall plant, you shall harvest (. Guru Granth Sahib 78)